Lipid components, fatty acids and triacylglycerol molecular species of black and red rices - Yoshida, Hiromi; Tomiyama, Yuka; Mizushina, Yoshiyuki (Food chemistry, 2010)
Extracted lipids obtained from black and red rices were analysed by high-performance liquid chromatography (HPLC), for endogenous tocochromanols. The molecular species and fatty acid (FA) distribution of triacylglycerols (TAG) isolated from these total lipids were analysed by a combination of AgNO 3 thin-layer chromatography (TLC) and gas chromatography (GC), and were investigated in relation to the content of endogenous tocochromanols. With a few exceptions, the predominant tocols were γ-tocotrienol and α-tocopherol, followed by α-tocotrienol (red) and γ-tocopherol (black) with much smaller amounts of β-, δ-tocopherols and δ-tocotrienol. The lipids of these rices were comprised mainly of TAG (76.4–80.5%), free FA (7.2–9.8%), and phospholipids (3.5–3.6%), whilst other components were present in minor proportions (0.1–4.1%). The principal FA components were palmitic (16:0), oleic (18:1 n − 9) and linoleic (18:2 n − 6) acids. Fifteen different TAG molecular species were detected and quantified by successive applications of AgNO 3-TLC and GC. The major TAG components were S 2M (7.0–7.8%), SM 2 (12.6–12.9%), M 3 (15.7–16.5%), SMD (23.5–23.7%), SD 2 (5.7–5.8%), M 2D (9.3–9.8%), MD 2 (8.1–8.6%) and D 3 (5.8–7.4%) (where S, M, D, and T denote a saturated FA, a monene, a diene, and a triene, respectively). The results suggested that these rice lipids contain large amounts of nutraceuticals with proven positive health effects.